2018
DOI: 10.1083/jcb.201612051
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic exosomes promote dendritic cell migration along guidance cues

Abstract: Inflammation stimulates lymphatic endothelial cells to release exosomes, which accumulate in the perivascular stroma. Brown et al. show that these exosomes promote the directional migration of dendritic cells along guidance cues in complex environments by enhancing dynamic cellular protrusions in a CX3CL1-dependent manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 70 publications
2
59
0
Order By: Relevance
“…A recent study has revealed that exosomes have cell motility control potential (Brown et al, ). To investigate the effect of exosomes on the migration of hBMSCs, a Transwell assay was performed, and the exosomes collected at different stages of osteogenesis were added into the lower chamber.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study has revealed that exosomes have cell motility control potential (Brown et al, ). To investigate the effect of exosomes on the migration of hBMSCs, a Transwell assay was performed, and the exosomes collected at different stages of osteogenesis were added into the lower chamber.…”
Section: Resultsmentioning
confidence: 99%
“…The IEα 52–68 traffics to the early endosome and then to the MIIC where it is loaded onto MHCII and efficiently presented by DC both in vivo and in vitro to restricted CD4‐T‐cells independently from the MCHII present onto the exosomes . Similarly, rejection of murine heart transplants is dependent on release of exosomes from donor DC which are taken up by host DC in local lymph nodes while activated human lymphatic endothelial cells secrete exosomes that express C‐X‐C chemokine receptor type 1 (CXCR1) ligand increasing migration of DC . Finally, iDC internalize exosomes released from mast cells pulsed with BSA or OVA via CD91 dependent pathway and this promotes their maturation and enables them to induce efficient CD4 T‐cell proliferation; by contrast, exosomes from macrophages and B‐cells were ineffective.…”
Section: Exosomesmentioning
confidence: 99%
“…EVs are thought to mediate cell-cell communication [1] and may carry a variety of proteins, lipids and RNA with potential to impact target cell physiology. It has been proposed that EVs modulate tumor environments to allow for tumor seeding and growth and promote angiogenesis [2][3][4][5][6][7][8]. EVs have also been implicated in the prion-like spread of neuropathogenic protein aggregates in several neurodegenerative diseases [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%